The Text of Conservatism: The Role of Abbas’ Ahl al-Sunnah wa al-Jamā‘ah in Underpinning Acehnese Current Religious Violence - Saifuddin Dhuhri (Studia Islamika, 2016)
Considerable studies have been undertaken on Islamic sects and radicalisation. There is, however, little work on textual analysis of traditionalist book, which is regarded as traditionalist collective identity.  This article is a critical analysis of the term Ahl al-Sunnah Wa al-Jama`ah, with special reference to Sirajuddin Abbas’ book. ; I`tiqad Ahl al-Sunnah Wa al-Jama`ah. His articulation of the concept Ahl al-Sunnah Wa al-Jama`ah plays great role in radicalising traditionalist ideology and providing traditionalist Islamic activists the justification to go against Wahhabism. His interpretation of the concept is, however, strongly rejected by Wahhabis, because of imposing hatred and intolerance against Wahhabism. By using Fairlough’s critical analysis, I studied critically the content of Abbas’s book. Some concepts related to the articulation of Ahl al-Sunnah Wa al-Jama`ah are chosen and analysed to find the role of the book in underlying traditionalist ideology. Then, Abbas’ interpretations of the selected concepts are verified through the method of interview to unearth ideological articulation of Abbas’.DOI: 10.15408/sdi.v23i1.2405